Mapping QTL for summer dormancy related traits in tall fescue (Festuca arundinacea Schreb.) - Talukder, Shyamal K.; Bhamidimarri, Suresh; Chekhovskiy, Konstantin; Saha, Malay C. (Scientific reports, 2020)
Summer dormancy is an important stress avoidance mechanism of cool season perennial grasses to persist well under harsh summer conditions. QTL associated with summer-dormancy related traits in tall fescue has significant breeding implications. An F 1 pseudo testcross population was developed by crossing a Mediterranean (103-2) to a Continental parent (R43-64). The population was genotyped using 2,000 SSR and DArT markers. Phenotyping was done in growth chambers and in two Oklahoma, USA locations. Total length of R43-64 and 103-2 maps were 1,956 cM and 1,535 cM, respectively. Seventy-seven QTL were identified in the male and 46 in the female parent maps. The phenotypic variability explained by the QTL ranged between 9.91 and 32.67%. Among all the QTL, five summer dormancy related putative QTL were identified in R43-64 linkage groups (LGs) 4, 5, 12, 20 and 22 and two in 103-2 LGs 5 and 17. All the putative summer dormant QTL regions in male map showed pleiotropic responses and epistatic interactions with other summer dormant and stress responsive QTL regions for plant height, new leaf and dry biomass weight. The flanking markers related to the QTL reported in this study will be useful to improve tall fescue persistence in dry areas through marker-assisted breeding.